2014
DOI: 10.5144/0256-4947.2014.465
|View full text |Cite
|
Sign up to set email alerts
|

The Saudi Abnormal Glucose Metabolism and Diabetes Impact Study (SAUDI-DM)

Abstract: BACKGROUND AND OBJECTIVESSaudi Arabia underwent opulence-driven socio-cultural and lifestyle changes leading to soaring rates of diabetes mellitus. This study exposes the epidemiology of abnormal glucose metabolism namely: diabetes and impaired fasting glucose (IFG) in 13 administrative regions of Saudi Arabia.DESIGN AND SETTINGSThis is a nationwide, household, population-based cross-sectional study that was conducted through primary health care centers during the period 2007–2009.PATIENTS AND METHODSA nationw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 32 publications
4
56
0
Order By: Relevance
“…Using any of the three classification criteria IFG, IGT and high HbA1c (5.7-6.4%), prediabetes was detected in 28.7% of the participants, which is much higher than the 11.9% prevalence reported previously in Jeddah, 14 but closer to an earlier national, household, population-based study of 22.6%. 28 The noted differences in prevalence estimates might be attributed to the different methods used for defining prediabetes, as well as the difference in age between the populations studied, since age is one of the strongest predictors of diabetes and prediabetes in various populations, [29][30][31] including our own. 14 Prediabetes was identified in only 7 individuals (or 4.0% of total people with prediabetes) using FPG, confirming the earlier suggestion of low sensitivity of FPG to detect diabetes and prediabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Using any of the three classification criteria IFG, IGT and high HbA1c (5.7-6.4%), prediabetes was detected in 28.7% of the participants, which is much higher than the 11.9% prevalence reported previously in Jeddah, 14 but closer to an earlier national, household, population-based study of 22.6%. 28 The noted differences in prevalence estimates might be attributed to the different methods used for defining prediabetes, as well as the difference in age between the populations studied, since age is one of the strongest predictors of diabetes and prediabetes in various populations, [29][30][31] including our own. 14 Prediabetes was identified in only 7 individuals (or 4.0% of total people with prediabetes) using FPG, confirming the earlier suggestion of low sensitivity of FPG to detect diabetes and prediabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also yielded similar results. A study on the entire Danish diabetic population (based on historical individual register data) showed that compared to patients with less education, diabetic patients with a higher level of education were approximately 26% less prone to mortality and 10-15% less prone to developing complications (24).…”
Section: Discussionmentioning
confidence: 99%
“…Incidences of diabetes mellitus have significantly increased in Saudi Arabia over the past decade. Al-Rubeaan et al (2014) found in a cohort of over 5000 subjects, abnormal glucose metabolism occurred in almost 35% of subjects. An investigation performed by Al-Nozha et al (2004) noted overall prevalence for diabetes mellitus in adults in Saudi Arabia was 23.7%.…”
Section: Introductionmentioning
confidence: 95%